Functional discourse grammar a typologically-based theory of language structure - Hengeveld, Kees, 1957-; Mackenzie, J. Lachlan (Oxford : Oxford University Press, 2008)
In this comprehensive presentation of functional discourse grammar, the authors set out its nature and origins and show how it relates to contemporary linguistic theory. They demonstrate and test its explanatory power and descriptive utility against linguistic facts from over 150 languages.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Functionalism (Linguistics); Grammar, Comparative and general